The lichens around the South Pole Syowa Station - Kawamata, Akinori; Kurosawa, Norio; Kosugi, Makiko; Imura, Satoshi; Kudoh, Sakae (2019)
The Tenth Symposium on Polar Science/Ordinary sessions : [OB] Polar Biology, Wed. 4 Dec. / Entrance Hall (1st floor) , National Institute of Polar Research conference object